PERLINDUNGAN HUKUM ATAS HAK PRIVASI DAN KERAHASIAAN IDENTITAS PENYAKIT BAGI PASIEN COVID-19 - Indah Maria Maddalena Simamora (PENERBIT LAFADZ JAYA, 2022)
Covid-19 patients are just like any other disease patient. Covid-19 patients also have the same rights and obligations as other patients. As in the Law of the Republic of Indonesia Number 36 of 2009 concerning Health in Article 5 paragraphs 1 and 2